2006
DOI: 10.1038/nature04600
|View full text |Cite
|
Sign up to set email alerts
|

CHIP-mediated stress recovery by sequential ubiquitination of substrates and Hsp70

Abstract: Exposure of cells to various stresses often leads to the induction of a group of proteins called heat shock proteins (HSPs, molecular chaperones). Hsp70 is one of the most highly inducible molecular chaperones, but its expression must be maintained at low levels under physiological conditions to permit constitutive cellular activities to proceed. Heat shock transcription factor 1 (HSF1) is the transcriptional regulator of HSP gene expression, but it remains poorly understood how newly synthesized HSPs return t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
345
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(373 citation statements)
references
References 26 publications
22
345
3
3
Order By: Relevance
“…CHIP interacts with HSC70 and HSP90 through its amino-terminal TPR domain, and the ubiquitin ligating reaction is performed by a U-box motif in its carboxy terminus. In association with these chaperones, CHIP plays an essential role in the quality control of misfolded proteins (Tateishi et al, 2004;Younger et al, 2004Younger et al, , 2006Qian et al, 2006).Here, we report that many of the MKKS mutants that are responsible for the MKKS/BBS diseases are degraded in the cell much more rapidly than the wild-type protein and that a CHIP-dependent ubiqutin-proteasome pathway plays a crucial role in this rapid degradation. Although the wildtype MKKS rapidly shuttles between the centrosome and cytosol, rapidly degraded MKKS mutants often fail to localize to the centrosome.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…CHIP interacts with HSC70 and HSP90 through its amino-terminal TPR domain, and the ubiquitin ligating reaction is performed by a U-box motif in its carboxy terminus. In association with these chaperones, CHIP plays an essential role in the quality control of misfolded proteins (Tateishi et al, 2004;Younger et al, 2004Younger et al, , 2006Qian et al, 2006).Here, we report that many of the MKKS mutants that are responsible for the MKKS/BBS diseases are degraded in the cell much more rapidly than the wild-type protein and that a CHIP-dependent ubiqutin-proteasome pathway plays a crucial role in this rapid degradation. Although the wildtype MKKS rapidly shuttles between the centrosome and cytosol, rapidly degraded MKKS mutants often fail to localize to the centrosome.…”
mentioning
confidence: 70%
“…CHIP interacts with HSC70 and HSP90 through its amino-terminal TPR domain, and the ubiquitin ligating reaction is performed by a U-box motif in its carboxy terminus. In association with these chaperones, CHIP plays an essential role in the quality control of misfolded proteins (Tateishi et al, 2004;Younger et al, 2004Younger et al, , 2006Qian et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CHIP has been implicated in progression of the pathophysiological conditions of various neurodegenerative diseases. 8,9,11,12,28,46,47 However, the molecular mechanisms regulating the functions of CHIP in these pathophysiologic conditions are not clearly elucidated. In the present study, we identify that CHIP and Cdk5 act as critical factors to regulate the level of the toxic protein, tAIF, during oxidative stress-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Based on these domains, it has been indicated that CHIP has a crucial role as a molecular co-chaperone in the maintenance of protein homeostasis during cellular stress and recovery. 8,[11][12][13] Indeed, CHIP has been demonstrated to serve as a crucial catalyst for ubiquitination of Hsp70 client proteins targeting for proteasome-dependent degradation. 11 The function of CHIP with its molecular chaperones has been well documented to reduce cellular toxicity associated with several neurodegenerative diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation